2011
DOI: 10.1089/ten.tea.2010.0475
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Smooth Muscle Cells from CaCl2-Induced Rat Aortal Expansions as a Surrogate Culture Model for Study of Elastogenic Induction of Human Aneurysmal Cells

Abstract: Regression of abdominal aortic aneurysms (AAAs) via regeneration of new elastic matrix is constrained by poor elastin synthesis by adult vascular cells and absence of methods to stimulate the same. We recently showed hyaluronan oligomers (HA-o) and TGF-b1 (termed elastogenic factors) to enhance elastin synthesis and matrix formation by healthy rat aortic smooth muscle cells (RASMCs). We also determined that these factors could likewise elastogenically induce aneurysmal RASMCs isolated from periadventitial CaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 38 publications
1
34
2
Order By: Relevance
“…6,7 Data from animal experiments examining AAA in a range of models, such as rat transplant, rat elastase, mouse calcium chloride, and mouse angiotensin II (AngII), however, suggest that TGF-β1 inhibits AAA development. [8][9][10][11] TGF-β1 activation is a multistep process. The TGF-β1 precursor interacts with a latency-associated peptide and forms a complex called small latent complex.…”
mentioning
confidence: 99%
“…6,7 Data from animal experiments examining AAA in a range of models, such as rat transplant, rat elastase, mouse calcium chloride, and mouse angiotensin II (AngII), however, suggest that TGF-β1 inhibits AAA development. [8][9][10][11] TGF-β1 activation is a multistep process. The TGF-β1 precursor interacts with a latency-associated peptide and forms a complex called small latent complex.…”
mentioning
confidence: 99%
“…Unlike collagen fibers, which undergo natural regenerative repair postdisruption, elastic fibers are poorly restored, due to poor elastogenesis, and impaired elastic fiber assembly by postneonatal and diseased vascular SMCs. 6,7,29,30 Thus, to achieve AAA growth arrest, elastin regeneration must significantly exceed its breakdown. 31 Previously, 10 we showed that BM-SMCs exhibit high elastogenesis and generate paracrine secretions that stimulate elastogenesis by EaRASMCs, findings which support their use for matrix regenerative AAA therapy, provided they can be efficiently delivered to the AAA wall.…”
Section: Discussionmentioning
confidence: 99%
“…As we previously published, 6,7 21-day cultures within Permanox chamber slides were fixed with 2% w/v cacodylate glutaraldehyde (12 h), postfixed in 1% w/v osmium tetroxide (1 h), dehydrated in a graded ethanol series (50-100% v/v), and embedded in Epon 812 resin. The sections were mounted on copper grids, stained with uranyl acetate and lead citrate, and visualized on a Hitachi TEM (Model H7600T).…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Elastogenic factors (EFs) were also added to stimulate cellular elastic matrix generation in this study, with the doses (i.e., 0.1 ng/mL transforming growth factor-beta 1 [TGF-b1] and 0.2 mg/mL hyaluronan oligomers [HA-o]) based on results obtained previously. 14 In light of results of other studies in our lab that demonstrate that human aortic smooth muscle cells (HASMCs) respond to elastogenic stimulation by EFs, 30 we have focused on study of this cell type to provide greater clinical relevance.…”
mentioning
confidence: 99%